The lived experience during the peri-diagnostic period of breast cancer: A scoping review. Issue 3 (March 2022) - Rogers, Courtney C.; Pope, Shannon; Whitfield, Francesca; Cohn, Wendy F.; Valdez, Rupa S.
Highlights: Burdens during this period are similar to those later in the cancer care continuum. Interventions at earlier points in the breast cancer care continuum are needed. More informational support is needed during this period. Shared decision making and patient navigation programs can provide support. Abstract: Objectives: The aim of this scoping review is to provide an overview of the existing research that investigates the lived experience during the peri-diagnostic period of breast cancer. Methods: Nine databases were searched for relevant literature between January 2007 and April 2019. Data were extracted and categorized using deductive and inductive approaches. Results: A majority of the 66 studies included used qualitative methods to retrospectively explore the treatment decision making process of female breast cancer patients. Patients experienced uncertainty, emotional distress, and a need for more information from providers and relied on social support and family guidance during this period. Conclusions: The results of this review show that the burdens experienced during the peri-diagnostic period parallel those in later periods of cancer care. However, these burdens are prompted by different circumstances. More research is needed to explore the lived experience during this period through the use of mixed-methods and by recruiting a diverse sample with regards to role in the breast cancer experience, age, gender, race, and ethnicity. Practice implications: Interventions positioned at earlier points in the breast cancer experience should provide informational support, which could be delivered through shared decision making models. Additional support could be facilitated by patient navigation programs and health information technology.